2018
DOI: 10.3390/ma11060875
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures Evolution and Micromechanics Features of Ni-Cr-Si Coatings Deposited on Copper by Laser Cladding

Abstract: Three Ni-Cr-Si coatings were synthesized on the surface of copper by laser cladding. The microstructures of the coatings were characterized by optical microscopy (OM), X-ray diffraction (XRD), and scanning electron microscopy (SEM) with an energy dispersive spectrometer (EDS). According to the analysis results of phase compositions, Gibbs free energy change and microstructures, the phases of three coatings appeared were Cr3Si+γ-Ni+Cuss (Coating 1, Ni-26Cr-29Si), Cr6Ni16Si7+Ni2Si+Cuss (Coating 2, Ni-10Cr-30Si) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…[36]. Cr 3 Ni-based phases identified in the coating were also reported in recent literature, showing high hardness and excellent toughness in thermally sprayed Co-based materials [37,38]. Apart from enhancing the solidus point of the alloy, it has recently been reported that a high amount of Cr has a positive effect (in the case of brazing powders) on the shear strength and activation of the solution strengthening mechanism of the alloy [39].…”
Section: Xrd Diffraction Measurementsmentioning
confidence: 65%
“…[36]. Cr 3 Ni-based phases identified in the coating were also reported in recent literature, showing high hardness and excellent toughness in thermally sprayed Co-based materials [37,38]. Apart from enhancing the solidus point of the alloy, it has recently been reported that a high amount of Cr has a positive effect (in the case of brazing powders) on the shear strength and activation of the solution strengthening mechanism of the alloy [39].…”
Section: Xrd Diffraction Measurementsmentioning
confidence: 65%
“…In agreement with Jin's group, joining Ni and Cu is desirable because of the formation of Ni-Cu solid solutions and phases that can enhance the hardness, corrosion, and wear properties of heat exchanger tubes. For example, the laser cladding technique enhanced the microstructural properties of Ni-Cr-Si coatings deposited on copper substrates by Zhang et al [70]. The findings revealed the formation of Ni 2 Si dendritic phases at the top and columnar grains at the bottom, having an average microhardness of 900 HV0.1 (Figure 11).…”
Section: Materials Selection For Heat Exchangersmentioning
confidence: 95%
“…On the one hand, this effectively improves the reflectivity of the substrate to the laser, increases the powder utilization rate, and lowers the cost due to the pre-placement of the powder on the surface of the Cu substrate. On the other hand, adding the appropriate amount of nickel elements can reduce the thermal conductivity of Cu substrates and promote the formation of a melt pool during the laser cladding process as a consequence of the infinite solid solution of nickel and copper in the phase diagram [ 14 , 15 , 16 ]. However, increasing the internal porosity, surface contamination, or severe oxidation during the cladding process represent the common problems associated with the introduction of intermediate layers using pre-setting methods such as bonding or thermal spraying [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%